AL-QUR'AN SEBAGAI PANDUAN HIDUP: PEMAKNAAN TEKSTUAL DAN KONTEKSTUAL DALAM KEHIDUPAN SOSIAL - Cempaka, Viola (Institut PTIQ Jakarta, 2024)
Differences in the way of understanding the text and context of the Qur'an can cause problems, especially when the principles of the Qur'an are applied in the social life of the community. One of the topics that often triggers debate is the issue of gender equality. This difference in understanding arises due to the various approaches used in interpreting the texts of the Qur'an. Along with technological advances and changes in the times, many modern scholars feel the need to interpret by paying attention to the context of today, so that the Qur'an can be a solution to the challenges faced by the ummah in the contemporary era. This research aims to discuss the importance of understanding the interpretation of the Qur'an both textually and contextually and its impact on social life. Using an analytical descriptive approach through literature studies, this study examines in depth the relationship between text and context in exploring the meaning of the Qur'an, as well as how it affects society. The results of the study show that textual interpretation leads to an understanding of meanings that are in accordance with the time and place of the Qur'an, while the contextual approach encouraged by modern scholars is more relevant and practical to apply in the lives of today's society.